Brain electrical activity in female Major Depressive Disorder patients - Lima, Marefa Tuz Zohora; Boby, Farjana; Zaman, Nusrut; Afroz, Sharmin; Morshed, Nahid Mahjabin; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2024)
Background: Quantitative EEG provides insight to the brain activity associated with depressive illness. Frontal asymmetry and changes of slow wave frequencies brain activity have been found as the characteristic features of Major Depressive Disorder (MDD). Objective: To assess the brain activity by power spectral analysis of EEG in female patients with MDD. Methods: This observational study was carried on 20 female MDD patients (age 20-40 years) enrolled from the Department of Psychiatry, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka. Twenty (20) healthy volunteers of the same age were considered the control group. For the study, EEG was recorded for 3 minutes in eye closed position by EEG data acquisition device, EEG Traveler BrainTech 32+ CMEEG-01, India. Power spectral analysis of EEG data was done by BT40 analysis software. For statistical analysis, the Mann-Whitney U test was done. Results: Significantly higher Absolute power of delta and theta brain wave, and lower alpha and beta brain wave activity was observed in female MDD patients compared to control in all most all electrodes in all cortical regions. Conclusion: MDD patients showed low excitable brain state and characteristic feature of high slow frequency wave and low fast frequency wave in MDD which can be diagnosed by quantitative EEG analysis. J Bangladesh Soc Physiol 2023;18(2): 53-62